2016
DOI: 10.1111/ejn.13426
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity of spontaneous spike frequency to sodium leak current in a Lymnaea pacemaker neuron

Abstract: The spontaneous rhythmic firing of action potentials in pacemaker neurons depends on the biophysical properties of voltage-gated ion channels and background leak currents. The background leak current includes a large K and a small Na component. We previously reported that a Na -leak current via U-type channels is required to generate spontaneous action potential firing in the identified respiratory pacemaker neuron, RPeD1, in the freshwater pond snail Lymnaea stagnalis. We further investigated the functional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
(74 reference statements)
3
3
0
Order By: Relevance
“…Consistent with the importance of intracellular Ca 2+ dynamics and homeostasis for neuronal function [78], we found that transcripts encoding the intracellular calcium release channels, ryanodine receptor and inositol triphosphate receptor, and voltage-gated Ca 2+ channel in L. stagnalis show the highest degrees of sequence similarity with their homologs in the other ve species (Figure 15). The non-selective Na + -leak channel NALCN also exhibited a high degree of sequence conservation between L. stagnalis and the other ve species, which is consistent with the necessary role of NALCN in regulating basal membrane potential in L. stagnalis [62,75], M. musculus [79], D. melanogaster [80], and C. elegans neurons [81]. Interestingly, a member of the TRP channel family, transient receptor potential melastatin 1 (TRPM1), also showed a moderate degree of sequence conservation between species.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with the importance of intracellular Ca 2+ dynamics and homeostasis for neuronal function [78], we found that transcripts encoding the intracellular calcium release channels, ryanodine receptor and inositol triphosphate receptor, and voltage-gated Ca 2+ channel in L. stagnalis show the highest degrees of sequence similarity with their homologs in the other ve species (Figure 15). The non-selective Na + -leak channel NALCN also exhibited a high degree of sequence conservation between L. stagnalis and the other ve species, which is consistent with the necessary role of NALCN in regulating basal membrane potential in L. stagnalis [62,75], M. musculus [79], D. melanogaster [80], and C. elegans neurons [81]. Interestingly, a member of the TRP channel family, transient receptor potential melastatin 1 (TRPM1), also showed a moderate degree of sequence conservation between species.…”
Section: Discussionsupporting
confidence: 74%
“…Consistent with the importance of intracellular Ca 2+ dynamics and homeostasis for neuronal function (Gleichmann and Mattson 2011), we found that transcripts encoding the intracellular calcium release channels, ryanodine receptor and inositol triphosphate receptor, and voltage-gated Ca 2+ channel in L. stagnalis show the highest degrees of sequence similarity with their homologs in the other five species (Figure 15). The non-selective Na + -leak channel NALCN also exhibited a high degree of sequence conservation between L. stagnalis and the other five species, which is consistent with the necessary role of NALCN in regulating basal membrane potential in L. stagnalis (Lu and Feng 2011;Lu et al 2016), mouse (Lu et al 2007), fruit fly (Moose et al 2017) and C. elegans neurons (Xie et al 2013).…”
Section: Discussionsupporting
confidence: 73%
“…L. stagnalis possesses a simple and well-characterized CNS that has been widely employed to elucidate key mechanisms of neural function (Syed et al 1990;Winlow and Syed 1992;Scheibenstock et al 2002;Silverman-Gavrila et al 2009;Rosenegger and Lukowiak 2010;Lu et al 2016) response to environmental pollutants (Bouétard et al 2013;Niyogi et al 2014;Crémazy et al 2018), and resistance to parasitic infection (Adema et al 1994). However, molecular characterization of the CNS has been impeded by the lack of a comprehensive transcriptome.…”
Section: Discussionmentioning
confidence: 99%
“…L. stagnalis possesses a simple and well-characterized CNS that has been widely employed to elucidate key mechanisms of neural function [2,4,[59][60][61][62][63], response to environmental pollutants [9,10,13], and resistance to parasitic infection [64]. However, molecular characterization of the CNS has been impeded by the lack of a comprehensive transcriptome.…”
Section: Discussionmentioning
confidence: 99%